Relational ethics meets principled practice in community research engagements to understand and address homelessness. Issue 4 (17th May 2021) - Hodgetts, Darrin; Rua, Mohi; Groot, Shiloh; Hopner, Veronica; Drew, Neil; King, Pita; Blake, Denise
Abstract: Growing homelessness in Aotearoa New Zealand stems primarily from rising inequalities and poverty. Drawing from scholarship on relational ethics, principled practice and Māori cultural concepts, this paper offers our reflections on nearly two decades of collective work to document and address homelessness. Central to the approach outlined are enduring community partnerships, the cultivation of reciprocal relations, and time spent with homeless people and those trying to work with them. We present exemplars for how we draw on everyday interactions with homeless people and agency staff to enhance local service and broader systemic responses to homelessness.